Autores y consenso - Manuel Caamaño Freire; Jenaro Graña Gil; Íñigo Hernández Rodríguez; José Antonio Mosquera Martínez; Susana Romero Yuste (Sociedade Galega de Medicina Interna, 2014)
Autores y consenso